Financial Management Calculations and Applications that affect Micro, Small and Medium Enterprises during and after the COVID-19 Pandemic - Basory, H.A.; Hellyani, C.A.; Pratama M.D. (Journal of Comprehensive Science (JCS), 2023)
The drastic economic changes caused by the COVID-19 pandemic have significantly affected Micro, Small and Medium Enterprises, MSMEs. In this study, we evaluate the financial management calculations implemented by MSMEs and the applications used to help them overcome the problems of increasing revenue generation, promotion, product knowledge and finance faced during and after the pandemic, we mention MSMEs Applications. Through online surveys and interviews with MSMEs, we found that most MSMEs experienced a decrease in revenue and liquidity issues during the pandemic. However, most MSMEs also admitted to using apps to help them manage their promotions as well as their finances, such as keeping track of marketing products, educating potential customers, expenses and income, managing receivables and payables, and seeking funding. Our results show that our financial management calculations and suggested MSMEs apps can help MSMEs overcome financial, revenue generation, promotion and product knowledge issues faced during and after the pandemic, but support from government and private institutions is needed to help MSMEs overcome liquidity issues and gain access to promotion and product knowledge. We also found that MSMEs that use apps are faster in adjusting to the conditions: digital business, changing economy and have better prospects in overcoming financial, promotion and product knowledge problems faced. The IT Adoption seems to have a positive perspective to support a sustainable development in MSMEs activities. We suggest that MSMEs can use the B.E.S.T financial management application and calculations that we presented in this journal, with financial efficiency and an estimated 150% increase in results with a 25% trial and error calculation.